Perceived School Fairness and Academic Functioning in Early Adolescents: Differential Associations for Adolescents with or Without ADHD? - Martinez, Andrew C.; Green, C. Danielle; Peugh, James L.; Becker, Stephen P. (Research on Child & Adolescent Psychopathology, 2026)
Although substantial research has focused on the academic outcomes of youth with attention deficit/hyperactivity disorder (ADHD), less is known about factors that promote positive adaptation among these youth in the school setting. Perceived fairness, a subcomponent of school climate, is associated with improved academic functioning and may play an important role among youth with ADHD who have been shown to display heightened reactions to injustice. This study examined perceived fairness in relation to academic functioning in early adolescents and whether this association differed for adolescents with or without ADHD. Participants were 341 early adolescents (ages 10–12), with approximately half (48.7%) diagnosed with ADHD. Teachers completed measures of learning problems and study skills, and adolescents completed measures assessing perceived fairness and attitude to school. Students with ADHD perceived their school to be less fair than students without ADHD, though the effect size was small. Regression analyses controlling for adolescent medication use, demographic characteristics, and co-occurring psychopathology revealed significant main effects wherein higher levels of perceived fairness predicted lower negative attitude to school, and ADHD status predicted a more negative attitude to school and lower study skills. A significant perceived fairness × ADHD interaction was found in relation to learning problems, wherein higher perceived school fairness was more strongly associated with fewer learning problems for students with ADHD than for students without ADHD. These findings contribute to research exploring promotive factors among adolescents with and without ADHD and have implications for interventions aiming to improve academic functioning.